Blueprint for revolution : how to use rice pudding, Lego men, and other nonviolent techniques to galvanize communities, overthrow dictators, or simply change the world - Popovic, Srdja, 1973-; Miller, Matthew I., 1979- (Random House, 2015)
"In Blueprint for Revolution, Srdja Popovic outlines his philosophy for implementing peaceful world change and provides a model for activists everywhere through stories of his own experience toppling dictatorships (peacefully) and of smaller examples of social change (like Occupy Wall Street or fighting for gay rights or zoning changes). Through examples of using laughter and music (e.g., Pussy Riot) to disarm the opposition and gather supporters, to staging a protest of Lego Men in Siberia (when flesh-and-blood people would have been shot), to a boycott of Cottage cheese in Israel to challenge price inflation while organizing around rice pudding to overthrow the dictator of the Maldives, Popovic uses true and sometimes outrageously clever examples of the ways in which non-violent resistance has achieved its means. Popovic argues in favor of non-violent resistance not for ideological reasons (as persuasive as those are) but because non-violence actually works better than violence. An inspiring (and useful!) guide for any activist--and a thoroughly entertaining read for any armchair politico"--